PENGEMBANGAN EVALUASI PEMBELAJARAN BAHASA ARAB BERBASIS DIGITAL PADA SMP MUHAMMADIYAH 10 SIDOARJO - Zahroo, Roosyidah Haniifah; By Arifin, Moch. Bahak Udin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of a wordwall website application-based evaluation tool is a development that provides convenience for students and teachers in implementing Arabic language learning evaluations. This study aims to determine the feasibility, flexibility, and accuracy of a digital wordwall website application-based evaluation tool in Arabic language learning at SMP Muhammadiyah 10 Sidoarjo. This study uses a development method or Research and Development with the ADDIE model with 5 stages: Analysis, Design, Development, Implementation, Evaluation. Data in this study were collected through questionnaires, interviews, observations, and documentation. Questionnaires were given to grade VIII students of SMP 10 Sidoarjo, interviews were conducted with Arabic language teachers, observations were carried out during product trials in the classroom, then documentation was taken from the tool testing process and through student learning outcomes. Furthermore, as a test of the feasibility of the product, the researcher used the assistance of validators in this study who were material experts, media experts, and Arabic language experts. According to the results of the expert validation test by the validator lecturer, the media product evaluation tool developed was said to be "very valid", as well as the response of students after carrying out the trial of the evaluation tool showed a high sense of enthusiasm during the application of the evaluation tool, this indicates that the product evaluation tool based on the wordwall website application developed is very valid and feasible to be applied in the Arabic language learning process of class VIIIC SMP Muhammadiyah 10 Sidoarjo.